(untitled) (Research, Society and Development, 2024)
Introduction: Cancer is a complex disease that encompasses more than 100 different types of malignancies. The disordered growth of cancer cells results in the formation of tumors, which can spread to other parts of the body. There are two main groups of cancer: carcinomas, originating in epithelial tissues, and sarcomas, originating in connective tissues. Objective: To describe the role of the multidisciplinary team in providing palliative care to cancer patients through a literature review. Methodology: The work was characterized as a literature review, with a descriptive and exploratory nature that used three databases, namely, Pubmed, SciELO and BVS, thus the publications that were indexed in more than one database were selected in the first search. The descriptors used were palliative care, and oncological patient, all extracted from DeCS (Health Sciences Descriptors). The guiding question was: What is the role of the multidisciplinary team in providing palliative care to cancer patients? Results: A team of different and complementary professionals from several fields plays a fundamental role in palliative care in oncology. In addition, they play a crucial role in educating patients and families about palliative care and promoting a patient-centered approach. Final Considerations: It is concluded that the multidisciplinary team is important in palliative care for oncology patients, considering that it is necessary to work in a differentiated, humanized way, prioritizing the patient’s well-being, comfort, and pain reduction. In addition, the recognition that reaching the end of life with dignity and respect is reinforced.